Urgency of Establishing Qanun on the Functional Duties of the High Prosecutor's Office in Aceh Province - Ridha Zikri; Thahir Luth; Aan Eko Widiarto (CV. AFDIFAL MAJU BERKAH, 2024)
The success and sustainability of the implementation of Islamic Shari'a in Aceh is not only the burden of local law enforcement agencies such as Wilayatul Hisbah, the Syar'iyah Court and the Islamic Shari'a Office, law enforcement agencies on a national scale are also involved such as the Indonesian National Police through the Aceh Regional Police and the Attorney General's Office in Aceh Province in charge of transferring Jinayat (Islamic criminal law) cases to the Syar'iyah Court. However, this task of the prosecutor's office is considered by the researcher to need improvement because the role of the prosecutor's office is responsible for the delegation of cases to 2 (two) different courts. Of course, this improvement is needed through Qanun which has legitimacy as a regional regulation in the Indonesian legal system. Based on this description, this research is a typology of normative (legal) research. The results and discussion in this study conclude: First, the area of Islamic shari'a law enforcement has a synchronization between Law Number 1 of 2021 concerning the Prosecutor's Office of the Republic of Indonesia with the Aceh Qanun in the enforcement of Islamic shari'a in Aceh. The presence of Islamic law enforcement agencies in Aceh does not mean that the task of enforcing Islamic law is only government agencies. Second, the Urgency of the establishment of Qanun Aceh Prosecutor's Functional Duty is a social condition that requires improvement in the enforcement of Islamic shari'a in Aceh